Stomatal response time to dynamic changes in ligth is essentially unaffected by growth light for three woody species - Freitas, Rafael Silva (2021)
Stomata are small epidermal pores responsible for the strict control of the amount of CO2 that diffuses into the leaves while controlling the amount of water vapor lost by them to the atmosphere. The time required for the stomatal valve opening and closing is coordinated with an optimized hydraulic supply and strongly responds to the surrounding environment. Here, we demonstrate that intense shading conditions promote high levels of plasticity in plants of Podocarpus macrophyllus, Eucalyptus urophylla, and Capsicum chinense, in a series of hydraulic, anatomical and gas exchange traits, parameters that have been associated with optimized stomatal kinetics. The high levels of plasticity expressed in the species that we observed (in leaf hydraulic conductance values as well as stomatal size, density, and length) did not necessarily translate into changes in stomatal kinetics, here assessed as the time required to change the initial stomatal conductance in 90%. Our findings demonstrate that, although these parameters are mechanistically involved in stomatal functioning and exhibit profound plastic behavior, a number of other factors that probably are insensible to light supply also dictate this process, rendering the stomatal response time to dynamic changes in light essentially unaffected by growth light conditions. Keywords: Hydraulic conductance. Irradiance. Light acclimation. Leaf Gas Exchange. Stomatal density.